Dinamika Pemikiran Fiqh dalam NU (Analisis atas Nalar Fiqh Pola Madzhab) - Ahmad Arifi (Universitas Islam Negeri Mataram, 2009)
Fiqh as a product of thoughts always faces changes and developments. Similarly, NU’s fiqh develops in line with NU communities’ dynamics. Therefore, differences and diversities in NU fiqh must exist. In this context, the principle of al-muhâfazhah ‘ala al-qadîm al-shâlih wa al-akhdz bi al-jadîd al-ashlah, which is attributed to NU, compromise two contradictory sides, that are classical heritage (al-turâts al-qadîm), which becomes a source and base for NU religiosity, and changing forces of eras and communities (al-tajdîd). This process, then, results in emergence of three groups in NU: the first accepts al-turâts as a final truth and a source for solving any problem in present communities, the second accepts al-turâts but it must be contextualized by considering communities’ benefits, the third views al-turâts as out of date and irrelevant to the present contexts so that individual interpretation and judgment (ijtihad) is a must.